Effective market segmentation for open distance learning institutions’ marketing strategy / Mohd Nazri Mohd Noor ...[et al.] - Mohd Noor, Mohd Nazri; Abdul Aziz, Azlina; Harun, Yanty Roslinda; Aminudin, Norsiah; Zakariah, Zulaikha (Universiti Teknologi MARA, 2021)
This study aims to examine prospective learners’ perceptions toward effective market segmentation strategies for Open Distance Learning (ODL) advertisements. A descriptive study was conducted to assess preferences based on the generational cohort. Self-administered questionnaires were used to obtain meaningful data from 282 potential learners in Malaysia. The potential learners were working adults based on generational cohorts, namely, Gen Z, Gen Y, Gen X and Baby Boomers. The study was conducted from October to December 2020. Based on the analysis, Substantiality and Accessibility between ODL institutions and the market were viewed by the majority of the respondents as more effective than Responsiveness and Identifiability. However, the standardised path coefficient shows that all variables are significant predictors of the effective market segmentation. Therefore, it is noteworthy to develop creative marketing strategies to attract the attention of a wider audience. The insights obtained can potentially assist ODL institutions to better understand the characteristics of effective market segmentation. The study adds to the existing marketing literature and has strong implications in both academic and ODL institutions, particularly regarding the aspect of prospective learners’ opinions pertaining to effective market segmentation.